Cluster Assembled Silicon-Lithium Nanostructures: A Nanowire Confined Inside a Carbon Nanotube - Orellana, Walter; Pino-Rios, Ricardo; Yañez, Osvaldo; Vásquez-Espinal, Alejandro; Peccati, Francesca; Contreras-García, Julia; Cardenas, Carlos; Tiznado, William (Frontiers in Chemistry, 2021)
We computationally explore an alternative to stabilize one-dimensional (1D) silicon-lithium nanowires (NWs). The Li12Si9 Zintl phase exhibits the NW (_∞^1)[Li_6 Si_5 ], which coexists with Y-shaped Si4 structures. Interestingly, this NW could be assembled from the stacking of the Li6Si5 aromatic cluster. The (_∞^1)[Li_6 Si_5 ] @CNT nanocomposite has been investigated with density functional theory (DFT), including molecular dynamics simulations and electronic structure calculations. We found that van der Waals interaction between Li’s and CNT’s walls is relevant for stabilizing this hybrid nanocomposite. This work suggests that nanostructured confinement (within CNTs) may be an alternative to stabilize this free NW, cleaning its properties regarding Li12Si9 solid phase, i.e., metallic character, concerning the perturbation provided by their environment in the Li12Si7 solid.